Book Review “Negeri Para Bedebah”, Tere Liye, PT Gramedia Pustaka Utama, Jakarta, ISBN: 9789792285529 (Universitas Negeri Semarang, 2022)
This novel has a political economy theme. In accordance with the theme, this novel raises a lot about economic and political issues. The setting of the place used in this novel is mostly in Jakarta. Apart from being in Jakarta, Thomas also spends a lot of time on his Pacific Cruise Ship. This is where after escaping for the umpteenth time, Thomas took his entourage to the Pacific ship which was at the yatch dock in the Thousand Islands area to simply avoid the police who wanted to arrest them. A very interesting novel for lovers of Tere Liye's novels to follow. The story in this novel is a work of fiction that is no less exciting than the real story that is happening in this country, this novel tells the story of Thomas as a true fighter who never betrays what he has said.